The costs of obesity - Rachel Griffith (Institute for Fiscal Studies (IFS), 2023)
Policies that aim to reduce the prevalence of obesity have been high on the policy agenda for many years - see, for example, DHSC (2020) and Dimbleby (2021). Understanding the costs associated with obesity is important for informing policy. Bell and Deyes (2022) have recently produced what are, to date, the most detailed estimates of the costs of adult obesity in the UK. This note puts those estimates in context, discusses what costs are missing from their analysis, and which of the costs included are most relevant for policymaking.
Keywords: 330; Health and social care; Health; Obesity